Students push and pull factors towards visiting Melaka / Nura Adila Mazlan, Siti Farizah Nordin and Wardiah Abdul Halim - Mazlan, Nura Adila; Nordin, Siti Farizah; Abdul Halim, Wardiah (2016)
This study is about travel motivation among students push and pull factors towards visiting Melaka. The problem of study is despite the increasing in market size of young travellers (students), their desire to travel is little known about their actual travel motivation. Firstly this study is to identify the highest and the lowest of push and pull factor towards students’ motivation to travel. Next this study is to identify students demographic towards student motivation factor and to know the overall push and pull factor that motivate students to travel. Based on literature review surrounding the topic, push and pull motivation factors are used to develop theoretical framework. These factor include novelty, culture, adventure, escape, relaxation, social contact and destination attractions. This study was conducted at UiTM Melaka Kampus Bandaraya among the students from two different faculties at the campus. This study was used non probability sampling and convenience sampling. Three questions were examine using quantitative data analysis. Results indicated that the students state relaxation as main motivation to visit Melaka. Meanwhile, the students show that the local food is main motivations that attract them to visit Melaka. The policy implications emerging from the findings are discussed. These include the university, researcher, government and industry player.